Metabolomics-Based Frailty Biomarkers in Older Chinese Adults - Pan, Yiming; Li, Yun; Liu, Pan; Zhang, Yaxin; Li, Bowen; Liu, Zuyun; Shui, Guanghou; Ma, Lina (Frontiers in Medicine, 2022)
Background/Objectives: Owing to accelerated population aging, health in older adults is becoming increasingly important. Frailty can reflect the health status and disease risks of the older adults; however, appropriate biomarkers for early screening of frailty have not been identified. Here, we applied metabolomics to identify frailty biomarkers and potential pathogenic mechanisms of frailty. Methods: Serum metabolic profiles from 25 frail and 49 non-frail (control) older adults were systematically investigated by liquid chromatography-mass spectrometry based metabolomics. Results: We identified 349 metabolites of 46 classes, with 4 increased and 7 decreased metabolites in frail older adults. Pearson correlation analysis identified 11 and 21 metabolites that were positively and negatively correlated with grip strength, and 7 and 76 metabolites that were positively and negatively correlated with gait speed, respectively. Pathway analysis identified 10 metabolite sets and 13 pathways significantly associated with one or more frailty phenotype criteria. Conclusions: These results revealed the metabolite characteristics of serum in frail older adults. Intermediates of carbohydrate metabolism (e.g., isocitrate, malate, fumarate, cis-aconitate, glucuronate, and pyruvate), saturated fatty acids (e.g., palmitic acid), unsaturated fatty acids (e.g., arachidonate and linoleic acid), and certain essential amino acids (e.g., tryptophan) may be candidate biomarkers for the early diagnosis of frailty. Mitochondrial function disorders, saturated fatty acid-mediated lipotoxicity, aberrant unsaturated fatty acid metabolism, and increased tryptophan degradation could be potential mechanisms of frailty.